Oxytocin Facilitates Empathic- and Self-embarrassment Ratings by Attenuating Amygdala and Anterior Insula Responses - Geng, YaYuan; Zhao, Weihua; Zhou, Feng; Ma, Xiaole; Yao, Shuxia; Becker, Benjamin; Kendrick, Keith M. (Frontiers in Endocrinology, 2018)
The hypothalamic neuropeptide oxytocin has been reported to enhance emotional empathy in association with reduced amygdala activation, although to date studies have not investigated empathy for individuals expressing self-conscious, moral emotions which engage mentalizing as well as emotion processing networks. In the current randomized, double-blind placebo controlled functional MRI experiment on 70 male and female subjects we have therefore investigated the effects of intranasal oxytocin (40 IU) on behavioral and neural responses to embarrassment experienced by others or by self. Results showed that oxytocin significantly increased ratings of both empathic and self-embarrassment and concomitantly decreased skin conductance response and activation in the right amygdala and insula but not in the medial prefrontal cortex. The amygdala effects of oxytocin were associated with the magnitude of the skin conductance response and trait anxiety scores. Overall our results demonstrate that oxytocin increases ratings of self- and other embarrassment and that this is associated with reduced physiological arousal and activity in neural circuitry involved in emotional arousal. The neural effects of oxytocin are also stronger in individuals with high trait anxiety suggesting that it may particularly reduce their anxiety in embarrassing situations.